Cholesterol efflux by high density lipoproteins is impaired in patients with active rheumatoid arthritis. Issue 7 (20th January 2012) - Charles-Schoeman, Christina; Lee, Yuen Yin; Grijalva, Victor; Amjadi, Sogol; FitzGerald, John; Ranganath, Veena K; Taylor, Mihaela; McMahon, Maureen; Paulus, Harold E; Reddy, Srinivasa T
Abstract : Objectives: Reverse cholesterol transport (RCT) is a major antiatherogenic function of high density lipoprotein (HDL). In the current work, the authors evaluated whether the RCT capacity of HDL from rheumatoid arthritis (RA) patients is impaired when compared to healthy controls. Methods: HDL was isolated from 40 patients with RA and 40 age and sex matched healthy controls. Assays of cholesterol efflux, HDL's antioxidant function and paraoxanase-1 (PON-1) activity were performed as described previously. Plasma myeloperoxidase (MPO) activity was assessed by a commercially available assay. Results: Mean cholesterol efflux capacity of HDL was not significantly different between RA patients (40.2%±11.1%) and controls (39.5%±8.9%); p=0.75. However, HDL from RA patients with high disease activity measured by a disease activity score using 28 joint count (DAS28>5.1), had significantly decreased ability to promote cholesterol efflux compared to HDL from patients with very low disease activity/clinical remission (DAS28<2.6). Significant correlations were noted between cholesterol efflux and the DAS28 (r=−0.39, p=0.01) and erythrocyte sedimentation rate, (r=−0.41, p=0.0009). Higher plasma MPO activity was associated with worse HDL function (r=0.41/p=0.009 (antioxidant capacity); r=0.35, p=0.03 (efflux)). HDL's ability to promote cholesterol efflux was modestly but significantly correlated with its antioxidant function (r=−0.34, p=0.03). Conclusions: The cholesterol efflux capacity of HDL is impaired in RA patients with high disease activity and is correlated with systemic inflammation and HDL's antioxidant capacity. Attenuation of HDL function, independent of HDL cholesterol levels, may suggest a mechanism by which active RA contributes to increased cardiovascular (CV) risk.